2019
DOI: 10.1126/scisignal.aau5755
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory neuron–specific SHP2-ERK signaling network regulates synaptic plasticity and memory

Abstract: Mutations in RAS signaling pathway components cause diverse neurodevelopmental disorders, collectively called RASopathies. Previous studies have suggested that dysregulation in RAS–extracellular signal–regulated kinase (ERK) activation is restricted to distinct cell types in different RASopathies. Some cases of Noonan syndrome (NS) are associated with gain-of-function mutations in the phosphatase SHP2 (encoded by PTPN11); however, SHP2 is abundant in multiple cell types, so it is unclear which cell type(s) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 58 publications
(105 reference statements)
2
41
0
Order By: Relevance
“…However, most of the key RAS-ERK components, such as NF1, SHP2, BRAF, and MEK1/2, begin to be expressed before either embryonic day 10 or 15, which are initiation time points of neurogenesis or astrogliogenesis, respectively [212]. Recently, it has been shown that the expression of RAS-ERK signaling molecules was remarkably different between excitatory and inhibitory neurons in mouse hippocampus [162]. Thus, it would be interesting to examine whether the expression levels of various signaling molecules are differentially regulated in NSCs over different developmental stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of the key RAS-ERK components, such as NF1, SHP2, BRAF, and MEK1/2, begin to be expressed before either embryonic day 10 or 15, which are initiation time points of neurogenesis or astrogliogenesis, respectively [212]. Recently, it has been shown that the expression of RAS-ERK signaling molecules was remarkably different between excitatory and inhibitory neurons in mouse hippocampus [162]. Thus, it would be interesting to examine whether the expression levels of various signaling molecules are differentially regulated in NSCs over different developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Omrani and colleagues showed that inhibitory neuron-specific attenuation of hyperpolarization-activated cyclic nucleotide-gated (HCN) currents can be an underlying mechanism for the cognitive deficits in Nf1 +/mice when they used an HCN agonist to rescue cognitive deficits in Nf1 +/mice [217]. Recently, Ryu and colleagues showed that selectively reducing the interaction between mutant SHP2 and Gab1 in excitatory neurons reversed the physiological and behavioral deficits in a mouse model of NS [162]. Conditional mutant mice with higher spatial and temporal resolution will provide clues when, where, and which cell types are most suited for interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SHP2 D61G/+ mice showed increased level of ERK activation only in excitatory neurons and enhanced glutamatergic synaptic transmission but no changes in inhibitory synaptic functions 32 . Ectopic expression of SHP2 D61G selectively in the excitatory but not in inhibitory neurons increased ERK activation and impaired spatial learning and LTP 19 . One explanation for these cell type-specific effects of RAS signalling is that the expression profiles of RAS-ERK signalling genes are significantly different between hippocampal excitatory and inhibitory neurons 19 .…”
Section: Discussionmentioning
confidence: 92%
“…In adult mice, Kras is expressed not only in inhibitory neurons but also in excitatory neurons 19 . To investigate the effects of ectopic KRAS G12V expression in the excitatory neurons on learning and memory, we injected AAV-KRAS G12V -HA into the dorsal hippocampus of αCaMKII-Cre mice ( Fig.…”
Section: Ectopic Expression Of Kras G12v In the Hippocampal Excitatormentioning
confidence: 99%